1997
DOI: 10.1002/(sici)1096-9063(199710)51:2<131::aid-ps614>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Polydisperse ethoxylated fatty alcohol surfactants as accelerators of cuticular penetration. 1. Effects of ethoxy chain length and the size of the penetrants

Abstract: : The e †ects of polydisperse ethoxylated fatty alcohol (EFA) surfactants on the penetration of six organic compounds varying in size (molar volumes, 107È282 cm3 mol~1) and lipophilicity (log 0É8È6É5) were investigated using K ow astomatous isolated cuticular membranes (CM) of Citrus and pear leaves. Mobilities of model compounds in CM were measured by unilateral desorption from the outer surface (UDOS). Rate constants (k*) obtained in these experiments are directly proportional to di †usion coefficients and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 34 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…No superior spreading probably took place in the presence of the high already PA-MPEG concentration, which is also a wetting agent on its own [ 23 , 27 ]. The lack of any significant influence on PA-MPEG efficacy by strong penetration enhancer, Genapol C 050, was at first surprising [ 41 , 42 ]. However, in the presence of 7.5% PA-MPEG in the spray, and assuming a cuticle/water partition coefficient of Genapol C 050 close to 1, the explanation of these results was that Genapol C 050 probably did not simply enter through leaf cuticles [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…No superior spreading probably took place in the presence of the high already PA-MPEG concentration, which is also a wetting agent on its own [ 23 , 27 ]. The lack of any significant influence on PA-MPEG efficacy by strong penetration enhancer, Genapol C 050, was at first surprising [ 41 , 42 ]. However, in the presence of 7.5% PA-MPEG in the spray, and assuming a cuticle/water partition coefficient of Genapol C 050 close to 1, the explanation of these results was that Genapol C 050 probably did not simply enter through leaf cuticles [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Surfactants containing aliphatic moieties and PEG chains of 10 to 15 ethylene oxide (EO) units in length have been shown to enhance the uptake of water soluble compounds (Baur et al 1997;Coret and Chamel 1994), and it has been suggested that they have significant hygroscopic properties Bukovac 1987a, 1987b). However, it was decided to add humectants to the existing formulation as opposed to formulating the herbicide with a high EO content surfactant for two reasons.…”
Section: Dose Response Experimentsmentioning
confidence: 99%
“…Surfactants are widely used in agrochemical applications . Non-ionic polyethoxylated surfactants are postulated to have the ability to sorb and retain water, , helping to keep the active ingredient in the spray deposit in a physical state, which favors its uptake into the leaf. , Therefore, the present work studied the humectant properties of selected non-ionic surfactants in a systematic approach. Comprehensive experimental data on the water sorption ability of commonly used non-ionic polydisperse surfactants at the full range of RHs up to 95% are presented.…”
Section: Discussionmentioning
confidence: 99%
“…A very prominent organic humectant is glycerol, which is commonly used in pharmaceutical, cosmetic, and food products to give them the desired flexibility, softness, and shelf life . In the context of plant protection agents, humectancy of non-ionic polyethoxylated surfactants is believed to be related to a high ethylene oxide (EO) content, because surfactants with a higher EO content enhance cuticular uptake of water-soluble active ingredients. In most ethoxylated surfactants, the hydrophilic moiety is composed of polyoxyethylene chains. Ethoxylated surfactants are thought to improve the uptake of hydrophilic and lipophilic herbicides by different modes of action .…”
Section: Introductionmentioning
confidence: 99%